Effects of repeated vigorous exercise on plasma antioxidant vitamins and urinary excretion of 8-hydroxy-2-deoxyguanosine - Doi, T.; Okamura, K.; Sakurai, M.; Hamada, K.; Yoshioka, Y.; Migita, T.; Mitsuzono, R.; Sumida, S. (Medicine & Science in Sports & Exercise, 1996)
The effects of repeated vigorous exercise on plasma antioxidant vitamin status and biomakers of oxidative stress in 10 well-trained long distance runners attending an 8-day training camp were assessed. It was found that plasma antioxidant vitamin status remained unchanged but oxidative damage occurred in the tissues including DNA. Implication. The effects of hard training selectively fatigue bodily structures and functions and do not show in a manner that might be evidenced in untrained persons.